1989
DOI: 10.1246/cl.1989.1005
|View full text |Cite
|
Sign up to set email alerts
|

Charge Carrier Transport Properties of Organopolysilanes and Their Application to Xerographic Photoreceptor

Abstract: Aiming application of the high hole drift mobility in organopolysilanes, the organopolysilane-based organic layered photoreceptors for electrophotography have been developed with phthalocyanine pigments as a photo-generating material. The photoreceptor combined with titanylphthalocyanine exhibited the high sensitivity of 1.8 cm2 (μJ)−1 at 780 nm and fairly good stability, suggesting the possibility for practical use of organopolysilanes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
24
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 10 publications
2
24
0
Order By: Relevance
“…Figure 3 shows the dependence of the square root of the electric field on the hole drift mobility for PS/SiO͑5͒, PS/SiO͑10͒, and PMPS. From this figure, it was found that the hole drift mobility of PMPS as a photoinjected charge carrier was near 10 Ϫ4 cm 2 V Ϫ1 s Ϫ1 at an electric field of 2ϫ10 5 V cm Ϫ1 , as cited in the literature, [1][2][3][4][5] and it increased with the square root of the electric field. Generally, PS/SiO͑5͒ and PS/SiO͑10͒ exhibited slightly lower hole drift mobility than PMPS in the electric field range of 1ϫ10 5 -7ϫ10 5 V cm Ϫ1 , depending on the pentamethyldisiloxanylpropylphenylsilane fraction in the copolysilanes.…”
supporting
confidence: 63%
See 1 more Smart Citation
“…Figure 3 shows the dependence of the square root of the electric field on the hole drift mobility for PS/SiO͑5͒, PS/SiO͑10͒, and PMPS. From this figure, it was found that the hole drift mobility of PMPS as a photoinjected charge carrier was near 10 Ϫ4 cm 2 V Ϫ1 s Ϫ1 at an electric field of 2ϫ10 5 V cm Ϫ1 , as cited in the literature, [1][2][3][4][5] and it increased with the square root of the electric field. Generally, PS/SiO͑5͒ and PS/SiO͑10͒ exhibited slightly lower hole drift mobility than PMPS in the electric field range of 1ϫ10 5 -7ϫ10 5 V cm Ϫ1 , depending on the pentamethyldisiloxanylpropylphenylsilane fraction in the copolysilanes.…”
supporting
confidence: 63%
“…A typical application of this phenomenon centers on organic polymeric electrophotographic receptors that have flexibility and mechanical toughness, utilizing its high hole drift mobility. [1][2][3][4][5][6] However, photo-oxidation during irradiation with ultraviolet light in air to produce the siloxane structure is also known to be a characteristic of organic polysilanes. 7 Polysilanes are generally sensitive to oxygen even in the dark without any other corrosive substances such as corona effluents to induce Si-Si scission or siloxane formation.…”
mentioning
confidence: 99%
“…This enables polysilylenes to show remarkable properties such as UV absorption, photoconductivity and thermochromism [2], in which case the polymer backbone acts both as a one-dimensional semiconductor and as a chromophore. Potential applications in the fields of electrophotography [5], data storage [6] and non-linear optics have resulted in increasing interest in these materials.…”
Section: Introductionmentioning
confidence: 99%
“…Polysilanes have been widely investigated from the interests on unique thermal [1 -3], optical [4 -6], electrochemical [7 -10] and electrical [11][12][13][14] properties originated from the delocalization of ¾ -electrons along the silicon backbone (see Refs [15,16] and references therein). Moreover, they can be applied to photo-and electroactive materials, such as photoresist [17], non-linear optical [18], photoluminescent [19] and electroluminescent [20] materials, which makes polysilanes interesting materials to be studied from both fundamental and industrial view points.…”
Section: Introductionmentioning
confidence: 99%